PERBANDINGAN METODE DOUBLE EXPONENTIAL SMOOTHNG DAN DOUBLE MOVING AVERAGE UNTUK PERAMALAN HARGA BERAS ECERAN DI KABUPATEN PAMEKASAN - Indah Listiowarni; Nindian Puspa Dewi; Andrey Kartika Widhy Hapantenda (Jurnal Komputer Terapan, 2020)
Rice is the main carbohydrate source used by Indonesians as a staple food, so the availability and price are also a concern. The purpose of this study is to forecast monthly rice prices for 2019, while comparing 2 forecasting methods namely Double Moving Average and Double Exponential Smoothing to get the best forecasting results of rice prices. The data used in this study is retail rice prices from January 2011 to March 2019. Based on the tests conducted, the Double Moving Average method is better with the MAPE value reaching 0.582542%, and the MSE value reaching 6349.25 using the time order 3. Average monthly retail price forecasts for 2019 using the DMA method of Rp.12,169, -